Susceptibility of Anopheles sinensis to Plasmodium vivax in malarial outbreak areas of central China - Guoding Zhu (2018)
Background: Anopheles sinensis, Anopheles anthropophagus, Anopheles minimus and Anopheles dirus are the major vectors of malaria transmission in China. Anopheles sinensis is considered a secondary vector due to its relatively low malaria-transmission ability. However, in 2005, an outbreak of over 40,000 Plasmodium vivax malaria cases was reported in areas where Anopheles sinensis was the only major vector. Therefore, it is necessary to reassess the malaria transmission ability of this vector species in China. Methods. Laboratory colonies of An. sinensis and An. anthropophagus, and first-generation progeny (F1) of An. sinensis that had been collected in central China, were infected by direct membrane feeding assay with mono-vivax gametocyte-containing blood collected from vivax-infected patients. The mosquitoes were kept for 7 to 14 days post-blood feeding to allow parasites to develop into oocysts and sporozoites. Infectivity was measured by dissecting midguts and salivary glands. The presence of oocysts and sporozoites was determined by microscopy at 7 and 14 days post-blood feeding, and the numbers of gametocytes and asexual parasites, as well as mosquito parasite infections, were determined. Results: The positive oocyst and sporozoite feed rates of the 142 pairs of lab-colony An. sinensis and An. anthropophagus were not significantly different, and the same results were found with the 10 pairs of laboratory and F1 An. sinensis. An. sinensis had more oocysts/midgut at 7 days post-feeding than An. anthropophagus, but the gametocytemia, asexual parasitemia, and ratio of macrogametocytes to microgametocytes, did not correlate with either oocyst or sporozoite infection. However, in the oocyst-positive mosquitoes, there was a correlation between gametocytemia and the average oocyst number/midgut. Conclusions: The susceptibility of An. sinensis (both laboratory and F1) to P. vivax-infected blood is similar to Anopheles anthropophagus, when evaluated by membrane feeding assay under laboratory conditions. In recent years, in central China, the vivax malaria transmission ability of An. sinensis has probably been underestimated. Further studies of this species in other regions are needed. An. sinensis could also be a good candidate vector for evaluating candidate malaria transmission-blocking vaccines (TBV). © 2013 Zhu et al.; licensee BioMed Central Ltd.